Analisa ukuran bulir mineral magnetik pada lindi tpa sampah kota padang menggunakan metoda Anhysteretic Remanent Magnetization (ARM) (Analysis of magnetic mineral grain size on leachate of Padang city waste landfill using the Anhysteretic Remanent Magnetization (ARM) method) - Risaldi Putra; - Mahrizal; Fatni Mufit (PILLAR OF PHYSICS, 2015)
Padang city has landfill located in Air Dingin Village Balai Gadang  Koto Tangah Subdistrict of Padang. This landfill has some leachates  that assumed there is seepage from leachate pond to the river and drain. The results observation present that the river is decomposed and its color is changed so it obliged to research about Pollutants of Landfill (TPA) Padang City Mineral Magnetic Basis. The purpose of the research is to determinate grain size and mineral magnetic domain in Leachates of Landfill (TPA) Padang City by using ARM (Anhysteretic Remanent Magnetization) Method. The samples research were 6 samples that taken from leachate pond, the river, and drain at landfill (TPA) area. Measuring instruments that utilized were Ekman Grab, Susceptibility Meter, Molsfin AF demagnetizer, PARM ( Partial Anhysteretic Remanent Magnetization) and Minispin Magnetometer. The data collection was analyzed by plotting the correlation between relative intensity (I/Io) and magnetic field by using Lowrie and Fuller Kurve Test as comparative kurve for measuring grain size and magnetic domain.  The research results showed that grain size of leachate pond sample is about 6 μm up to 135 μm, whereas grain size of river and drain samples are about 110 μm up to 135 μm. Magnetic domain sample was obtained of the research result is pseudo single domain (PSD) and multi domain (MD). Grain size was obtained from river and drain sample bigger than grain size of leachate pond sample. Mineral magnetic of leachate pond is more disposed to PSD whereas mineral magnetic of river and drain is more disposed to  MD. Based on the results, the river and drain samples are expected that it has contaminated mineral magnetic of leachate pond (anthropogenic)